Methods study on Bandolino shoes - Mendoza, Ma. Eleanor; Olegario, Audrey; Ong, Michael U.; Pardinas, Michael D.; Pulido, Ma. Rowena P. (College of Engineering, 1991)
Bandolino was the site chosen by our group where to conduct methods study. Located in Marikina, Bandolino is a shoe factory housed in a two-storey building. The plant is divided into two divisions : the upper-making division on the second floor and the shoe-lasting division on the first floor. Objectives were set by the group, the major of which is the application of the different techniques taught in the Methods Engineering Class, particularly in conducting a methods study. Direct observation, interview and work measurement were the methods used in documenting the present system of Bandolino. Restrictions and criteria were also set to determine the extent of our study. Five categories were identified as problem areas. These are operations, layout, materials handling, materials storage and working conditions. Several alternatives with respect to each problem area were considered, analyzed and evaluated. The advantages and disadvantages of the alternatives were pitted against each other; afterwhich, a proposed system was drawn up. To facilitate faster and better understanding of this paper, charts, diagrams and figures are also presented as supplementary informations.